Replication Data for "Income, Consumer Preferences, and the Future of Livestock-Derived Food Demand" - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This dataset contains the data and scripts required to reproduce the tables and figures in the study titled "Income, consumer preferences, and the future of livestock-derived food demand." R scripts were run using R version 4.0.5 on Windows 10 x64. All the data and script should be placed in one folder. Add a R project into the folder (for example, "project_ldfDemand.Rproj"). Open the R project before running the scripts. The scripts (extension .R) are ordered sequentially, and should be run sequentially for the first time. The script "22masterFile.R" is the master file that runs all scripts sequentially from start to finish. The study generated simulation results in GAMS. The GAMS code is not part of the scripts in this dataset. Please direct any questions on the GAMS code and input data to Adam Komarek (a.komarek@uq.edu.au)